The Moderating Role of Exchange Rate Volatility on Economic Factors and Financial Performance of Multinational Corporations in Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: This study investigate the moderating role of exchange volatility on the relationship between economic factors and the financial performance of multinational corporations (MNCs) in Nigeria. The research adopted an ex-post facto research design, and the secondary data was collected from 2013 to 2022. The sample consisted of twenty chosen from the leading forty MNCs in Nigeria based on data availability, and multiple regression was used to establish the moderating effect of exchange rate volatility on these economic relations. The economic variables analyzed show that ROE is sensitive to the oil price, interest rate, and foreign reserves with an indication that an increased oil price and a low interest rate is an added advantage to its financial performance while low foreign reserves and high exchange rate volatility decrease ROE. Also, exchange rate volatility moderate the effect of these economic factors on ROE as evidenced in this study. Therefore, this study conclude that economic stability such as foreign reserves and exchange rates are relevant determinants of MNCs Financial performance in Nigeria. This study strongly recommends that MNCs adopt various risk management techniques, including currency management strategies, to address issues that threaten their stability. In this respect, the government needs to make efforts to strengthen the foreign reserves and control other economic variables favorable for MNCs. Further, the policies require MNCs in the oil-dependent industries to put in place strategies that may help contain variations in performance in line with the level changes in exchange rate volatility or other economic factors essential in maintaining performance in Nigeria’s volatile economy.